Yüksek sıcaklık süperiletkenlerinde paramagnetik meissner olayı - Özuğur, Bengü (My University, 2004)
PARAMAGNETIC MEISSNER EFFECT in HIGH TEMPERATURE SUPERCONDUCTORS In this thesis, an experimental data of real and imaginary part of magnetic moment of the mixed phase of Hg-Ba-Ca-CuO (Hg-1212/ 1223) superconducting sample, which displays the Meissner critical transition temperature of about 140oK under normal atmospheric pressure, had been synthesized by Ü. Onbaşlı, was used. An alternative (ac) magnetic moment measurements had been performed by the Quantum Design SQUID (Superconducting Quantum Interference Device) magnetometer, by applying a weak ac magnetic field of 1Gauss. The detailed mathematical and physical studies of Paramagnetic Meissner Effect, which becomes observable within the imaginary component of the ac magnetic moment, have been done in this work. The intrinsic property of superconductors has exhibited the diamagnetic attitude below the Meissner critical transition temperature, . On the other hand, when a weak magnetic field is applied to pure, single crystal or very cleanly prepared polycrystalline sample, a paramagnetic tendency can be observed in a temperature range near . To find out the scientific reasons of this paramagnetic tendency and its occurrence, the Paramagnetic Meissner Effect has been investigated by means of both determining some special temperature values such as thermodynamic equilibrium temperature. Moreover, for designation of convenient mathematical functions to diamagnetic and paramagnetic response of the system and the spin re-organization in the context of -wave pairing mechanism of PME have been investigated. Furthermore, a phase angle difference of 900 has been found between the real and imaginary components of magnetic moment at around Meissner critical transition temperature. The phase difference mentioned above, that was determined to be relevant for the mixed phase of CuO2 layered Hg-1212/ 1223 high temperature superconductors which contains intrinsic Josephson junctions, confirming the -wave pairing mechanism. Furthermore, it was understood that the value of this phase difference is in a good agreement with the phase which is necessary for the formation of -junctions [17]. June, 2004 Bengü Özuğur

YÜKSEK SICAKLIK SÜPERİLETKENLERİNDE PARAMAGNETİK MEİSSNER OLAYI Bu tezde, Ü. Onbaşlı tarafından sentezlenen, kritik Meissner geçiş sıcaklığı normal atmosferik basınçta yaklaşık 140K olan, karışık fazlı süperiletken Hg-Ba-Ca-CuO (Hg-1212/ 1223) numunesinin magnetik momentinin gerçek ve sanal kısımlarının deneysel verileri kullanılmıştır. Alternatif (ac) magnetik moment ölçümleri 1Gauss'luk zayıf bir alternatif magnetik alan uygulanarak Kuantum Dizayn SQUID (Süperiletken Kuantum Girişim Cihazı) magnetometreyle gerçekleştirilmiştir. Bu çalışmada alternatif magnetik momentin sanal bileşeninde gözlenebilir hale gelen Paramagnetik Meissner Olayı'nın detaylı matematiksel ve fiziksel incelemesi yapılmıştır. Süperiletkenlerin asli özelliği, Meissner kritik geçiş sıcaklığı 'nin altında diamagnetik davranış sergilemeleridir. Diğer taraftan saf, tek kristal veya çok temiz hazırlanmış polikristal numunelere zayıf bir magnetik alan uygulandığında civarında, belirli bir sıcaklık aralığında paramagnetik bir eğilim gözlenebilmektedir. Bu paramagnetik eğilimin ve oluşumunun bilimsel sebeplerini bulmak için, Paramagnetik Meissner Olayı; hem termodinamik denge sıcaklığı gibi sistemin bazı özel sıcaklık değerlerinin belirlenmesi, sistemin diamagnetik ve paramagnetik cevabına uygun matematiksel fonksiyonların tespiti bağlamında, hem de -dalga çiftlenimi mekanizması çerçevesinde, spinlerin yeniden organizasyonu bağlamında araştırılmıştır. Ayrıca magnetik momentin gerçek ve sanal bileşenleri arasında yaklaşık olarak Meissner geçiş sıcaklığı civarında 90o'lik faz açısı farkı bulunmuştur. Yukarıda bahsi geçen faz farkının, kendine has Josephson kavşakları içeren CuO2 katmanlı Hg-1212/ 1223 karışık fazlı yüksek sıcaklık süperiletkeni için, -dalgası çiftleniminin geçerli olduğu mekanizmasını doğruladığı tespit edilmiştir. Ayrıca, bu faz değerinin; -kavşaklarının [17] oluşumu için gerekli olan faz ile uyumlu olduğu anlaşılmıştır. Haziran, 2004 Bengü Özuğur
Keywords: Süper İletkenler